Effect of Ambarella Leaf Extract in Reducing Total Cholesterol Levels and Body Weight of Mice with Diabetes Mellitus Type II - Adhitama, Shendy; Kuswanti, Nur; Khaleyla, Firas (LenteraBio : Berkala Ilmiah Biologi, 2023)
Obesity has a high risk in developing diabetes mellitus (DM) because of the accumulation fat can reduce cell sensitivity. Ambarella leaf contain flavonoids which have the potential to reduce total cholesterol levels. This study aimed to determine the effect of ambarella leaf extract in reducing total cholesterol levels, body weight, and the most effective extract of diabetic mice type II. This study was an experimental research with Completely Randomized Design (CRD). This study used 24 male mice which were divided into 6 groups namely KN (normal), KP (DM), KM (metformin), K1 (extract 250 mg/kgBB), K2 (350 mg/kgBB), and K3 (450 mg/kgBB). Measuring total cholesterol levels used an EasyTouch meter. Weight measurement used digital scales. Data of cholesterol levels and body weight were analyzed using ANOVA test. The results showed that ambarella leaf extract had effects of total cholesterol levels and body weight (p>0.05). The best effect was shown by a dose of 450 mg/kgBB (K3). In conclusion, ambarella leaf extract have effect of reducing total cholesterol levels and body weight in mice with DM type II and the dose of ambarella leaf extract 450 mg/kgBB is the most effective dose of reducing total cholesterol levels and body weight in mice with DM type II.